A Brief Survey on Some Essentials of Portuguese Museum Law - Laureano, Abel (Museologia e Patrimônio, 2014)
The legal discipline of Portuguese museums is contained, as to its fundamental aspects, in a framework-act that establishes, explicitly, a comprehensive list of general principles governing this area. The Portuguese legal order uses a concept of "museum", which reflects its adherence to new paths trodden by Museology, namely the openness of museums to Society and the imperative of the museums' dynamism. In addition, and representing other key aspects, the framework-act establishes the freedom of creating museums, as well as a wide range of museological functions. This study refers, furthermore, to the topics of human and financial resources of museums, of museums' facilities, as well as of the creation, ownership and public access to museums.